'Welcome in my back Yard' – the role of affective practices and learning in an experiment with local social integration in Hjortshøj, Denmark. (10th May 2018) - Fallov, Mia Arp; Jørgensen, Anja
Abstract: This article is about how to understand community action and development of the commons can play a key role in societal integrative processes in increasingly segregated Scandinavian societies. More specifically it relates to the residents' integration of sixteen young adults with intellectual disabilities in Hjortshøj, what we might call a Danish intentional community. What might be learned from the example of Hjortshøj is, that it is not the segregation of residents in an ecological village, which alone accounts for the success of the experiment, nor is it solely due to the altruistic orientations of the existing residents. Rather, the integration process is dependent on inter-related affective practices of belonging, relating to the dimensions of local attachment, a common good, and normalization. Thus, integration is dependent on complex forms of relationality and how these affective practices form an affective subject characterized by emergence, flexibility, and diversity. By applying a conceptualization of Hjortshøj as a learning machine, the article provides insights to the complex assemblage of materiality, spatiality, and relationality in the local community of Hjortshøj, underlining how communities become machines for learning acts of citizenship.